Optimalisasi Terapi Okupasi Menggambar Terhadap Perubahan Tanda Dan Gejala Halusinasi Pada Pasien Dengan Gangguan Persepsi Sensori Halusinasi Di Rsjd Dr. Rm. Soedjarwadi Klaten - Fannisa Luthfiani; Sitti Rahma Soleman; Wahyu Reknoningsih (STIKes Ibnu Sina Ajibarang, 2024)
Schizophrenia is one of the most challenging mental disorders compared to other mental disorders. The clinical manifestations of schizophrenia are characterized by symptoms of psychopathology; positive symptoms (delusions and hallucinations), negative symptoms (motivational disorders, spontaneous reduction of words, and social interactions), as well as cognitive disorders. Hallucinations are a symptom of mental disorders in individuals which are characterized by changes in sensory perception such as feeling false sensations in the form of sound, sight, touch, taste and smell. Symptoms of hallucinations can be overcome one of them is by occupational therapy drawing. To determine the results of the implementation of occupational drawing therapy on changes in signs and symptoms of hallucinations in patients with hallucinatory sensory perception disorders. The research design used in this study was a descriptive design with a case study approach and was applied to 2 respondents with a pre test and post test. The results obtained between before and after applying occupational therapy drawing, the condition of both respondents showed a decrease in signs and symptoms of hallucinations, namely in respondent I from 11 to 9 and in respondent II from 9 to 5. Occupational therapy drawing can reduce signs and symptoms. hallucinatory symptoms in patients with hallucinatory sensory perce`ption disorders at RSJD Dr. RM. Soedjarwadi Klaten.